Afetos e engajamento político : experiência familiar na criação de uma associação de pessoas com doença falciforme - Silva, Karolyne Sebastiane da (2022)
Sickle Cell Disease (SCD) is a chronic, genetic and hematological pathology common in Brazil and commonly identified in the black population, however it is not restricted to this population. This disease causes repercussions in different intensities in the life of the sick person, the family and caregivers and in the different spheres of daily life, demanding commitment and dedication to continuous care given the chronicity involved. The experience of individuals and families with illness encompasses a subjective and personalized dimension not dissociated from the objective and collective dimension of the socio-historical and political context, placed in the circumstances of daily life and in the insertion in the social structure added, still, to the course of the illness. and treatment. In daily living with chronic illness, informal and formal social support influences the repercussions, of which we highlight that coming from the family and specific associations, respectively. Therefore, the objective of this study was to understand the family experience with the creation of an Association of people with SCD in the state of Mato Grosso from the affective and sociopolitical motivations that mobilized the engagement. This is a qualitative study from a socio-anthropological perspective, with data from comprehensive interviews with the Mother, the Father and a Son, members of the aforementioned Association. To deal with the data, we used the life trajectory, locating remarkable aspects and events of the family experience with the SCD, involved in the creation of the Association. Of the three children, the first had severe symptoms and complications of SCD, including two strokes, and lived for about 32 years. The second has mild symptoms and is the current vice president of the Association. The third died at 10 months of age. The daily coexistence with the SCD in the care of the three children imposed frequent contact with health services, exposing them to institutional racism, while promoting to the Mother and Father the knowledge through the experience that was extended to the collective when they engaged in the Association where care is more important. scale. Thus, it can be concluded that the associations reflect and translate demands related to SCD, taking them out of the personal and family sphere and moving them to the public space, for example, influencing specific public policies and, in this case, having repercussions with the struggles for Health of the Black Population in dialogue and strengthening with the comprehensive cause of the Black Movement